Anaphora resolution in near-native speakers of Italian - Sorace, Antonella; Filiaci, Francesca (Second language research, 2006)
This study presents data from an experiment on the interpretation of intrasentential anaphora in Italian by native Italian speakers and by English speakers who have learned Italian as adults and have reached a near-native level of proficiency in this language. The two groups of speakers were presented with complex sentences consisting of a main clause and a subordinate clause, in which the subordinate clause had either an overt pronoun or a null subject pronoun. In half of the sentences the main clause preceded the subordinate clause (forward anaphora) and in the other half the subordinate clause preceded the main clause (backward anaphora). Participants performed in a picture verification task in which they had to indicate the picture(s) that corresponded to the meaning of the subordinate clause, thus identifying the possible antecedents of the null or overt subject pronouns. The patterns of responses of the two groups were very similar with respect to the null subject pronouns in both the forward and backward anaphora conditions. Compared to native monolingual speakers, however, the near-natives had a significantly higher preference for the subject of the matrix clause as a possible antecedent of overt subject pronouns, particularly in the backward anaphora condition. The results indicate that nearnative speakers have acquired the syntactic constraints on pronominal subjects in Italian, but may have residual indeterminacy in the interface processing strategies they employ in interpreting pronominal forms.